Comparative metabolomic profiling of phenolics in the desiccation-tolerant “resurrection plant” Myrothamnus flabellifolia (Myrothamnaceae) using conventional and green chemistry-based solvent systems - Bentley, Joanne (Department of Molecular and Cell Biology, 2019)
Myrothamnus flabellifolia (Myrothamnaceae) belongs to a group of ±300 angiosperm species known as “resurrection plants” that exhibit vegetative desiccation tolerance. They are able to survive dehydration to an air-dry state, tolerating up to 95% cellular water loss for a prolonged period of time followed by the rapid recovery of metabolism in the tissues within 24–72 h of rehydration. Prolonged cellular water loss is deleterious and is associated with the production of reactive oxygen species (ROS), which causes cellular degeneration, and ultimately, death. Resurrection plants have evolved various strategies to ameliorate this damage, including biochemical, ultrastructural, and anatomical modifications. Myrothamnus flabellifolia is widespread across southern Africa, and within its range it occurs in regions that experience high, moderate, and low rainfall; the low rainfall region also being associated with longer dry periods. Myrothamnus flabellifolia has historically been used for the treatment of chest infections, uterine pain, and gingivitis, and, more recently, has been shown to exhibit various phytochemical activities relating to the potential inhibition of diabetes, reverse transcriptases, and microbes. Previous studies have found M. flabellifolia extracts to contain high levels of polyphenolic compounds, which act as protectants against the ROS-induced damages caused by prolonged periods without moisture. However, a global assessment of the phenolic constituents, including anthocyanins, present in M. flabellifolia from across its geographic range is currently lacking. As the biosynthesis of compounds is likely to be subject to a fair amount of environmental control, an evaluation of the molecules present in this species from across its geographic range is warranted. Thus, in this study, a liquid chromatography-tandem mass spectrometry (LC-MS/MS) metabolomics approach was used to screen for phenolic compounds, including anthocyanins, from leaf material sampled in the field from eight populations representing the western, southern, and eastern range of the species distribution. Putative phenolic compounds were identified based on their MSE spectra in the negative ionisation and positive ionisation (for anthocyanins) modes. Their potential roles in the ROS-scavenging capacity of this plant were also discussed. Using this information, multivariate statistics were used to compare the phenolic profiles of the different populations in order to ascertain whether plants from the different regions were associated with any particular phenolic signature, and this was also evaluated against a phylogenetic hypothesis for species relationships based on three non-coding chloroplastic markers. Additionally, a preliminary green chemistry-based extraction protocol using Natural Deep Eutectic Solvents was also used to further screen for phenolic compounds, and this was compared against the conventional organic solvent system. Several phenolic compounds not previously detected in M. flabellifolia were putatively identified, many of which, based on an assessment of the literature, are associated with high antioxidant activity. The phylogenetic analyses suggested that the Namibian plants are more highly diverged than the South African and Malawian plants. The metabolomics analysis corroborated the DNA analysis, in that the most differentially expressed ions in the Namibian population were able to discriminate these samples from both the Malawian and South African samples. While the phenolic profiles of the samples collected from the same countries were similar, there was reasonable withinpopulation variability in those collected from South Africa and Malawi. Conversely, the Namibian samples exhibited far less variability, suggesting that a particular suite of protective compounds may be required for survival in that comparatively drier region. A Natural Deep Eutectic Solvent-based system successfully targeted phenolics in M. flabellifolia and thus constitutes a potential future green chemistry solution for phytochemical investigations in medicinal plants.